Relation of mitochondrial oxygen consumption in peripheral blood mononuclear cells to vascular function in type 2 diabetes mellitus. (February 2014) - Hartman, Mor-Li; Shirihai, Orian S; Holbrook, Monika; Xu, Guoquan; Kocherla, Marsha; Shah, Akash; Fetterman, Jessica L; Kluge, Matthew A; Frame, Alissa A; Hamburg, Naomi M; Vita, Joseph A
Recent studies have shown mitochondrial dysfunction and increased production of reactive oxygen species in peripheral blood mononuclear cells (PBMCs) and endothelial cells from patients with diabetes mellitus. Mitochondria oxygen consumption is coupled to adenosine triphosphate (ATP) production and also occurs in an uncoupled fashion during formation of reactive oxygen species by components of the electron transport chain and other enzymatic sites. We therefore hypothesized that diabetes would be associated with higher total and uncoupled oxygen consumption in PBMCs that would correlate with endothelial dysfunction. We developed a method to measure oxygen consumption in freshly isolated PBMCs and applied it to 26 patients with type 2 diabetes mellitus and 28 non-diabetic controls. Basal (192±47 vs 161±44 pmoles/min, p =0.01), uncoupled (64±16 vs 53±13 pmoles/min, p =0.007), and maximal (795±87 vs 715±128 pmoles/min, p =0.01) oxygen consumption rates were higher in diabetic patients compared to controls. There were no significant correlations between oxygen consumption rates and endothelium-dependent flow-mediated dilation measured by vascular ultrasound. Non-endothelium-dependent nitroglycerin-mediated dilation was lower in diabetics (10.1±6.6 vs 15.8±4.8%, p =0.03) and correlated with maximal oxygen consumption ( r = −0.64, p =0.001). In summary, we found that diabetes mellitus is associated with a pattern of mitochondrial oxygen consumption consistent with higher production of reactive oxygen species. The correlation between oxygen consumption and nitroglycerin-mediated dilation may suggest a link between mitochondrial dysfunction and vascular smooth muscle cell dysfunction that merits further study. Finally, the described method may have utility for the assessment of mitochondrial function in larger scale observational and interventional studies in humans.